Structural performance of steel-concrete sandwich beams with carbon nanofiber reinforcement. (15th May 2019) - Faghih, Faezeh; Ayoub, Ashraf S.
Highlights: The performance of steel-concrete (SC) systems is enhanced through the use of hybrid fibers in the concrete core. The hybrid fibers include a combination of macro and nano-scale fibers, steel fibers and carbon nanofibers respectively. An overall fiber content percentage of 1.5% was deemed sufficient to alter the failure mode from brittle to ductile. Experimental investigations on representative SC specimens confirmed the benefits gained from using hybrid fibers. Abstract: Cementitious materials such as concrete are typically characterised as quasi-brittle with low tensile strength and low strain capacity, which hence affect the long-term durability of the structure. One of the most important issues in designing and maintaining massive concrete structures like offshore and nuclear power plants is concrete cracking, which is due to the low tensile strength of concrete. This can destroy the structural aesthetic and lead to deterioration of the structure. The addition of fibers to concrete has been proven to be a good mean to control its crack behaviour and maintain its ductility in tension. Further, since the discovery of carbon nanotubes/fibers (CNT/CNF), they have been also considered as efficient fibers for construction materials such as concrete. This study presents the structural performance of steel-concrete (SC) elements with a fiber reinforced concrete (FRC) core using both single and hybrid fibers (i.e. consisting of two types of fibers). For this study carbon nanofibers, and steel fibers which are conventionally used in practice, are used for the FRC. Static tests were conducted on eight SC beams with different concrete types. The paper reports on the experimental results obtained from four-point flexural loading of the SC beams. The study shows considerable improvement for both the strength and ductility of the tested specimens. The research laid the groundwork for additional in-depth studies on using carbon nanofiber reinforced concrete within structural members.